2019
DOI: 10.3390/en13010055
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Energy and Emissions Properties of Waste from Various Species of Mint in the Herbal Products Industry

Abstract: The paper presents the results of research on the physicochemical properties of plant biomass consisting of four mint species, these being Mentha × piperita L. var. citrata Ehrh.-'Bergamot', Mentha × rotundifolia L., Mentha spicata L., and Mentha crispa L. The research conducted consisted of the technical analysis of biofuels-determining the heat of combustion and the calorific value of the material under study, and the content of ash, volatile compounds, and humidity. In addition, elemental analysis was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The dust emission index, related to the ash content of the individual raw materials, is the highest for WRON (5.31 kg•Mg −1 ) and the lowest (14% lower) for WSBL (4.57 kg•Mg −1 ). The analysis of the emission factors showed that the analyzed biomass is characterized by higher emission rates relative to mint [46], tree leaves [47], rice straw [48], similar to eucalyptus globulus wood [49] and larch needles [34] and lower relative to jackfruit peel and jackfruit seeds [32]. Nevertheless, in relation to hard coal [33], it is characterized by low emissions in terms of the analyzed factors, which indicates that this fuel as environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%
“…The dust emission index, related to the ash content of the individual raw materials, is the highest for WRON (5.31 kg•Mg −1 ) and the lowest (14% lower) for WSBL (4.57 kg•Mg −1 ). The analysis of the emission factors showed that the analyzed biomass is characterized by higher emission rates relative to mint [46], tree leaves [47], rice straw [48], similar to eucalyptus globulus wood [49] and larch needles [34] and lower relative to jackfruit peel and jackfruit seeds [32]. Nevertheless, in relation to hard coal [33], it is characterized by low emissions in terms of the analyzed factors, which indicates that this fuel as environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol formation reactions: (8) Char is assumed as a solid carbon represented by the element carbon (C). Further cracking reactions simultaneously precede at both gas and solid phases as explained by the following Equations ( 9) to ( 14) [46]:…”
Section: Pyrolysis Processmentioning
confidence: 99%
“…Several conversion processes such as physical, thermal, biochemical-microbial and chemical have been utilized to transform biomass into energy [7,8]. It is important to note that the treatment of wastes is essential due to the restrictions in disposal, which are mainly related to cost and space.…”
Section: Introductionmentioning
confidence: 99%
“…This is very important when assessing the environmental impact of coarse-energy crops, i.e., emissions during thermochemical conversion from the burning. Typically, scientists research and evaluate emissions in the airflow [13][14][15][16]. The coarse-energy crops and their biomass studied for this article were assessed in a comprehensive manner, i.e., not only their calorific value and ash content but also their ash melting properties and pollutants emitted during the thermochemical conversion.…”
Section: Introductionmentioning
confidence: 99%